PEMIKIRAN FIQIH TGH. M. SALEH HAMBALI BENGKEL LOMBOK - Fadli, Adi (JURNAL PENELITIAN KEISLAMAN, 2012)
Thought Jurisprudence of Tuan Guru Bengkel which was built in locality-based fiqh in the worship and muamalah has raised controversy. Through the library research on these thoughts, reinforced by interviews, content analysis, and external and internal criticism, the following results were obtained: first, local jurisprudence thought of Tuan Guru Bengkel was the response to the social dynamics of the Sasak people of Lombok at the time. The concept of how propaganda was taught by the Prophet Muhammadâs kha>tib alna> s hasba âuqu>lihim had been practiced by Tuan Guru Benkel; second, the process of tafhi>m al-ummah by Tuan Guru Bengkel in the areas of worship and muamalah was based on strong arguments to adopt the Sha>fiâiy school of thought which, although not binding on anyone to adopt other school of thoughts on conditions that they know the details of their argument. His consistency in following the school of thought indicated his fat}anah to provide the firm attitude of the Sasak people of Lombok at that time in order to arrive at the stability of heart in worship and muamalah. His adaptive and contextual propagation made him as one of the pioneers of Islamic revival and renewal in Lombok.